Analisis Sistem Pendukung Keputusan dalam Pemilihan Obat untuk Pasien Diabetes Menggunakan Metode Multi Criteria - Dede Sunandar (Riau Jurnal Teknik Informatika, 2025)
Choosing the right medication for diabetic patients is a complex challenge, given the large number of drug alternatives available and the various criteria that must be considered, such as effectiveness, side effects, cost, ease of use, availability, drug interactions, and patient satisfaction. Improper decisions can negatively impact the patient's health and the effectiveness of treatment. This research aims to develop a decision support system that can assist in the selection of the most appropriate diabetes medication based on relevant criteria, thereby improving the quality of treatment and patient satisfaction. To achieve this goal, this study uses the Analytic Hierarchy Process (AHP) method, which allows paired comparisons between criteria and drug alternatives. This method gives weight to each criterion and calculates a score for each drug alternative based on the assessment made. This study involved six alternative diabetes drugs, namely Metformin, Glibenclamide, Acarbose, Sitagliptin, Liraglutide, and Canagliflozin. The assessment criteria used included effectiveness, side effects, cost, ease of use, availability, drug interactions, and patient satisfaction. Data were collected through questionnaires and analysis was carried out using the AHP method to determine the weighting of the criteria and final score for each drug. The results of the analysis showed that Sitagliptin had the highest score, making it the best choice for diabetic patients based on predetermined criteria. This research provides valuable insights for medical professionals in making decisions regarding drug selection, as well as improving patients' understanding of available treatment options.